Post-illumination pupil response after blue light: Reliability of optimized melanopsin-based phototransduction assessment. (October 2015) - van der Meijden, Wisse P.; te Lindert, Bart H.W.; Bijlenga, Denise; Coppens, Joris E.; Gómez-Herrero, Germán; Bruijel, Jessica; Kooij, J.J. Sandra; Cajochen, Christian; Bourgin, Patrice; Van Someren, Eus J.W.
Abstract: Melanopsin-containing retinal ganglion cells have recently been shown highly relevant to the non-image forming effects of light, through their direct projections on brain circuits that regulate alertness, mood and circadian rhythms. A quantitative assessment of functionality of the melanopsin-signaling pathway could be highly relevant in order to mechanistically understand individual differences in the effects of light on these regulatory systems. We here propose and validate a reliable quantification of the melanopsin-dependent Post-Illumination Pupil Response (PIPR) after blue light, and evaluated its sensitivity to dark adaptation, time of day, body posture, and light exposure history. Pupil diameter of the left eye was continuously measured during a series of light exposures to the right eye, of which the pupil was dilated using tropicamide 0.5%. The light exposure paradigm consisted of the following five consecutive blocks of five minutes: baseline dark; monochromatic red light (peak wavelength: 630 nm, luminance: 375 cd/m 2 ) to maximize the effect of subsequent blue light; dark; monochromatic blue light (peak wavelength: 470 nm, luminance: 375 cd/m 2 ); and post-blue dark. PIPR was quantified as the difference between baseline dark pupil diameter and post-blue dark pupil diameter (PIPR-mm). In addition, a relative PIPR was calculated by dividing PIPR by baseline pupil diameter (PIPR-%). In total 54 PIPR assessments were obtained in 25 healthy young adults (10 males, mean age ± SD: 26.9 ± 4.0 yr). From repeated measurements on two consecutive days in 15 of the 25 participants (6 males, mean age ± SD: 27.8 ± 4.3 yrs) test–retest reliability of both PIPR outcome parameters was calculated. In the presence of considerable between-subject differences, both outcome parameters had very high test–retest reliability: Cronbach's α > 0.90 and Intraclass Correlation Coefficient > 0.85. In 12 of the 25 participants (6 males, mean age ± SD: 26.5 ± 3.6 yr) we examined the potential confounding effects of dark adaptation, time of the day (morning vs. afternoon), body posture (upright vs. supine position), and 24-h environmental light history on the PIPR assessment. Mixed effect regression models were used to analyze these possible confounders. A supine position caused larger PIPR-mm (β = 0.29 mm, SE = 0.10, p = 0.01) and PIPR-% (β = 4.34%, SE = 1.69, p = 0.02), which was due to an increase in baseline dark pupil diameter; this finding is of relevance for studies requiring a supine posture, as in functional Magnetic Resonance Imaging, constant routine protocols, and bed-ridden patients. There were no effects of dark adaptation, time of day, and light history. In conclusion, the presented method provides a reliable and robust assessment of the PIPR to allow for studies on individual differences in melanopsin-based phototransduction and effects of interventions. Highlights: A method for quantifying melanopsin-dependent phototransduction is proposed. The quantification is based on the post-illumination pupil response after blue light. The presented method had very high test–retest reliability. Post-illumination pupil response differed between supine and upright position.